شعرية الإضمار في الخطاب الصوفي عند ابن الفرض والششتري - حماده, حمزة (University of El-oued, 2020)
لملخص يُعد الخطاب الصوفي من أكثر الخطابات الأدبيّة خصوصية، لما تتفرّد به اللغة الصوفية من مميّزات لغوية وبلاغيّة، وهذه الخصوصية تعود - في الأساس- إلى طبيعة التجربة الصوفية والممارسات العرفانية الذوقية التي يقوم بها السالك من أجل الوصول إلى التجلي الإلهي، فالتجربة الصوفية هي البنية العميقة التي تتغلغل فيها ذاتيّةُ الصّوفي، والصّوفيون أنفسُهم قد لوّحوا إلى هذه الحالة، التي لا يمكن التّعبير عنها بحروف العبارة لضيقها، وحدود نفسها، فكانت الإشارة الفضاء الموعود. Abstract: Sufi discourse is one of the most private literary discourses, as the Sufi language has unique linguistic and rhetorical characteristics. This specificity is essentially due to the nature of the Sufi experience and the gnostic practices performed by the traveler in order to reach the divine theophany. The mystical experience is the deep structure, in which the Sufi’s subjectivity permeates, and the Sufis themselves have mentioned the state, which cannot be expressed in words, the signal was the promised space.
مقال. Ex Professo. مج5. ع.1. جامعة الوادي
Keywords: الكلمات المفتاحية: الشعرية – الضمار – الرمز – التصوب – األدبية – الت ر،ة الصو; Keywords: Poetics - Ellipsis - Symbol - Sufism - Literary - Sufi.